Abdominal hysterectomy versus total laparoscopic hysterectomy in cases of enlarged uterine size - Raslan, Mohamed Attia; Morsi, Ahmed Tawfeek; Borg, Hesham Mohamed; Angioni, Stefano; Salem, Hesham A. El Aziz (International Surgery Journal, 2022)
Background: Total laparoscopic hysterectomy (TLH) is a feasible, efficient way to manage benign uterine pathology, and is better than standard abdominal hysterectomy as it offers less postoperative discomfort, shorter hospitalization, rapid recovery, and early return to daily living activities. Methods: A retrospective comparative cohort study was done on patients with abnormal uterine bleeding due to large myomas in the Department of Obstetrics and Gynecology, Tanta University Hospital, Tanta, Egypt, and Institute of Obstetrics and Gynecology, Cagliari University, Cagliari, Italy. Participants were classified into two groups. Group I (Laparoscopy group) included 20 patients for whom TLH was done. Group II (Laparotomy group) included 20 patients for whom open hysterectomy (OH) was done. Results: Our result revealed that statistically significant differences were observed between the studied groups in post-operative Hb value, postoperative return of bowel sounds, and amount of blood loss however, prolonged duration of surgery was noticed in laparoscopic group than laparotomy group. Conclusions: TLH is an accessible technique and an alternative to laparotomy when it was done by experienced surgeons for large uteri regardless of the site, size.